2009
DOI: 10.1016/j.jcta.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Spherical two-distance sets

Abstract: A set S of unit vectors in n-dimensional Euclidean space is called spherical two-distance set, if there are two numbers a and b so that the inner products of distinct vectors of S are either a or b. It is known that the largest cardinality g(n) of spherical two-distance sets does not exceed n(n + 3)/2. This upper bound is known to be tight for n = 2, 6, 22. The set of mid-points of the edges of a regular simplex gives the lower bound L(n) = n(n + 1)/2 for g(n).In this paper using the so-called polynomial metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 11 publications
1
51
0
Order By: Relevance
“…Musin proved this corollary by using a polynomial method in [20]. This corollary is used in proof of Theorem 4.13 in this paper.…”
Section: Corollary 34 Let X Be a Two-distance Set And A Innmentioning
confidence: 77%
See 1 more Smart Citation
“…Musin proved this corollary by using a polynomial method in [20]. This corollary is used in proof of Theorem 4.13 in this paper.…”
Section: Corollary 34 Let X Be a Two-distance Set And A Innmentioning
confidence: 77%
“…Optimal twodistance sets in S 6 are given from three Chang graphs or the set of midpoints of edges of a regular simplex in R 7 . Moreover, Musin [20] determined D S * d (2) for 7 d < 40. …”
Section: Classifications Of Optimal Two-distance Setsmentioning
confidence: 99%
“…This estimate was recently improved in [13] where it was shown that if the inner products between distinct code words take values t 1 , t 2 , and t 1 + t 2 ≥ 0, then |C| ≤ 1 /2n(n + 1). The proof relies on the method of linearly independent polynomials.…”
Section: Spherical Codesmentioning
confidence: 99%
“…Recently an improvement of the Delsarte-Goethals-Seidel bound on spherical s-codes for the case s = 2 was obtained in second author's paper [13]. Following this result, Nozaki [14] proved a general bound on the size of spherical s-codes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed we have a natural upper bound for the size of an s-distance set in R d , that is, |X| d+s s [2,4]. The largest cardinality of s-distance sets is known for several dimensions and s (see [7,9,12,20,23,25,26,31]). From the view point of distance sets, we want to obtain a small-dimensional representation of a graph.…”
Section: Introductionmentioning
confidence: 99%